Findings from a Structured Adaptation Process for the SafeCare Parenting Program to Address Family Needs in a Diverse Refugee Community. (July 2022) - Self-Brown, Shannon; Weeks, Erin A.; Perry, Elizabeth W.; Lee, NaeHyung; Rivers, Danielle E. S.; Reuben, Katherine; Rao, Nikita; O'Connor, Mary Helen; Feinberg, Iris; Willging, Cathleen; Whitaker, Daniel J.
Social workers can promote resiliency among refugee families by referring them to evidence-based programs to reduce the stressors of resettlement. The purpose of this study was to complete a structured adaptation process with the SafeCare® program for implementation in a refugee resettlement community. Participants included 21 members of an adaptation team made up of administrators, supervisors, and family service providers from three community agencies and community health workers. Quantitative findings suggested that content, process, and literacy-related adaptations were necessary to ensure cultural relevance of program materials. Qualitative feedback suggested the adaptation approach was a meaningful process that engaged community members and resulted in an acceptable and feasible curriculum for delivery in the refugee resettlement community, which will be further tested in a forthcoming implementation trial. The multi-pronged, community-engaged approach to SafeCare adaptation is presented as a potential framework for other programs that could benefit refugee children and their families.